The impact of contemplative practices on foreign language anxiety and learning - Scida, Emily E.; Jones, Jill E. (Studies in Second Language Learning and Teaching, 2017)
This study looked at the impact of the integration of contemplative practices on foreign language anxiety, positive and negative affect, self-efficacy, classroom climate, and language learning in students enrolled in an advanced intermediate Spanish language course in the USA. Data included pre- and post-test surveys, exam scores to measure learning outcomes, student interviews, and course evaluations. In the contemplative group, students engaged in brief 10-minute contemplative practices once a week, while the non-contemplative group followed the same syllabus but was not exposed to contemplative practices. Analysis of the data showed no significant differences in foreign language anxiety, self-efficacy or affect between the non-contemplative and contemplative groups at post-test but significantly higher scores on classroom climate measures in the contemplative group. Significantly higher grades were found on course exams for students in the contemplative group. Analysis of the pre-/post-survey data revealed a significant decrease in foreign language anxiety in both groups over the semester but not for affect or self-efficacy. This study extends the existing research on contemplative practices to a new context—affect and learning in foreign language courses.